Research on Identity Ethics and the Reconstruction of Social Relationships in Metaverse Virtual Spaces - Cai, Zixuan (Pinnacle Academic Press Proceedings Series, 2026)
In the era of the Metaverse, identity construction and the reconstruction of social relationships in virtual spaces have become an increasingly important and complex field of academic research. This study aims to comprehensively explore the multifaceted ethical issues related to user identity in Metaverse virtual spaces and their profound impact on contemporary social relationships. With rapid technological development, users' identities in virtual environments are no longer strictly limited to their real-life physical selves; instead, they are diversely constructed and continuously modified through advanced digital means. This unprecedented trend has inevitably given rise to numerous critical ethical issues, such as identity theft, the deliberate dissemination of false identities, and their detrimental impact on fundamental trust within digital social networks. Furthermore, novel interaction patterns in virtual spaces have fundamentally changed the formation, evolution, and maintenance of traditional social relationships. Consequently, users' behavioral expressions and intricate social network relationships within these emerging virtual communities need to be rigorously reexamined. Through a robust combination of qualitative and quantitative research methods, this study conducts an in-depth, systematic analysis of the ethical challenges surrounding identity construction in Metaverse environments. It further evaluates their direct impact on the redefinition of interpersonal relationships, ultimately aiming to provide solid theoretical support and actionable practical guidance for future virtual space design, ethical framework development, and effective user governance.